Fungicide Management of Faba Bean Gall (Olpidium viciae) in Ethiopia - Wulita Wondwosen Kebede; Mashilla Dejene W/Michael; Negussie Tadesse; Seid Ahmed Kemal (Turkish Journal of Agriculture: Food Science and Technology)
Various biotic, abiotic and socio-economic factors negatively affect the productivity of the crop. Among these, a new disease known as Faba bean galls (Olpidium viciae) has become a serious threat to faba bean production and productivity in highland areas of central and northern Ethiopia. Thus, field experiment was conducted in Lay Gorebela and Mush to assess the efficacies of fungicides for the management of faba bean gall under natural infection. Six fungicides were evaluated alongside control in randomized complete block design in three replications. Fungicides showed different levels of efficiency at both locations in both seasons. In 2014/15, the highest percent severity index and area under disease progress curve were calculated from control plots at both locations. At Lay Gorebela, higher grain yields were recorded from Metalaxyl 8% + Mancozeb 64% WP and Triadimefon 250 g/L sprayed plots whereas plots sprayed with Metalaxyl 8% + Mancozeb 64% WP gave higher yield at Mush. Similar trends in percent severity index and grain yield were observed with control treatment in 2015/16. Percent severity index and area under disease progress curve were negatively correlated with grain yield and positively correlated with each other at both locations and seasons. Partial budget analysis indicated as Triadimefon 250 g/L and Metalaxyl 8% + Mancozeb 64% WP were cost-effective. The chemical treatment could be used as a short-term control strategy, and a component in integrated management of faba bean galls.